Multilevel Approach of Factors Influencing Child Marriage among Bangladeshi Women: Data from the 2017-18 Bangladesh Demographic and Health Survey - Islam, Md Ariful; Islam, Md Kamrul; Md Al Mamun, Abu Sayed; Rana , Md Sohel; Hossain, Md Golam (International Journal of Statistical Sciences, 2023)
Child marriage is defined as the marriage of individuals below the age of 18 and is considered a violation of children's rights. The study aimed to determine the prevalence of child marriage among women in Bangladesh and identify the associated factors. This study utilized data from the Bangladesh Demographic and Health Survey (BDHS-2017-18) to analyze a sample of 18,851 ever-married women in Bangladesh. Chi-square test and multilevel logistic regression model was used in this study. By employing this statistical approach, the study aimed to uncover significant factors that contribute to the occurrence of child marriage in the country. The prevalence of child marriage among Bangladeshi women was 73.6%. The multilevel logistic regression model revealed several significant risk factors for child marriage among women in Bangladesh were; division (p<0.01), place of residence (p<0.01), women's and their husbands' education level (p<0.01), number of family members (p<0.01) and religion (p<0.01). The median age at first marriage among Bangladeshi women has been decreasing but still it is a great problem in the nation. This study emphasize the need for targeted interventions and policy measures to address the root causes of child marriage, such as improving access to education, promoting gender equality, and raising awareness about the negative consequences of early marriage on the well-being and development of children. Efforts should be made to empower women and girls, enhance their agency, and create an enabling environment that protects their rights and promotes their overall well-being. International Journal of Statistical Sciences, Vol. 23(2), November, 2023, pp 63-73